HUBUNGAN POLA ASUH ORANG TUA DENGAN KEPRIBADIAN PESERTA DIDIK - Sari, Trio Desva (Bimbingan dan Konseling, 2014)
A way of parents behavior and mothered to children is consisted mothering is consistend relatively. Family environment, as a place for a child to grow up and develop will influence toward childrens personality, especially from how parents raise and educate their children. This study aimed to describe: (1) A parents mothered toward childrens personality, (2) Students personality illustration in school, (3) A parents mothered with students personality in MTsTI Batang Kabung. Type of this study is describe quantitative correlation with population of students in VIII and IX in MTsTI Batang Kabung totally 267 students and 72 samples. Sampling using stratified random sampling. The instrument that is used to collecting data is a questionnaire. To analyze the data systems and children personality data using percentage analysis technique, meanwhile testing of hypothesis to see relationships take care of parents system between childrens personality by using pearson product moment correlation formula, the calculation using computer with Microsoft exel program and SPSS program version 16.00. The results of data analysis: (1) A parents mothered toward childrens personality in quite well category with the percentage 33,33 %, (2) childrens personality in fairly high category with percentage 41, 66 %, (3) A parents mothered with students personality with of founded rhitung 0,299> rtabel 0,227 on 72 df with significance 0,011 (sig <0,05). So, the result is faunded that relationships between take care of parent system with childrens personality in VIII and IX in MTsTI Batang Kabung at low significant level.